Characterization of Foot-and-Mouth Disease Virus's Viral Peptides with LC-ESI-MS - Ozdemir, Zafer Omer; Karahan, Mesut; Karabulut, Erdem; Mustafaeva, Zeynep (CHEM SOC PAKISTAN, 2010)
Peptides and proteins play a central role in numerous biological and physiological processes in living organisms. Viral capsid peptides are part of the viruses' outer shell of genetic materials. Viruses are recognized by immune system via capsid peptides. Depending on this property of capsid peptides, prototypes synthetic peptide-based vaccine can be developed. In this work, we synthesized three different viral peptide sequences of foot-and-mouth disease virus with microwave enhanced solid phase synthesis method. These peptides were characterized by using liquid chromatography electrospray interface mass spectrometry (LC-ESI-MS) with electro spray ionization. We briefly describe the essential facts for peptide characterization.
Keywords: Chemistry